Fractional-order control systems : fundamentals and numerical implementations - Xue, Dingyü (Fractional calculus in applied sciences and engineering., 2017)
This book explains the essentials of fractional calculus and demonstrates its application in control system modeling, analysis and design. It presents original research to find high-precision solutions to fractional-order differentiations and differential equations. Numerical algorithms and their implementations are proposed to analyze multivariable fractional-order control systems. Through high-quality MATLAB programs, it provides engineers and applied mathematicians with theoretical and numerical tools to design control systems. ContentsIntroduction to fractional calculus and fractional-order controlMathematical prerequisitesDefinitions and computation algorithms of fractional-order derivatives and IntegralsSolutions of linear fractional-order differential equationsApproximation of fractional-order operatorsModelling and analysis of multivariable fractional-order transfer function MatricesState space modelling and analysis of linear fractional-order SystemsNumerical solutions of nonlinear fractional-order differential EquationsDesign of fractional-order PID controllersFrequency domain controller design for multivariable fractional-order SystemsInverse Laplace transforms involving fractional and irrational OperationsFOTF Toolbox functions and modelsBenchmark problems for the assessment of fractional-order differential equation algorithms.